Ethnoecological Study of Ndhas Gendhing Spring in Sukorejo Village, Magelang Regency, Province of Central Java - Christian Donuke Sabasti; Daniel Dermawan Liyanto; Evelyn Valencia Wahyudi; Fajar Adinugraha (Otus Education: Jurnal Biologi dan Pendidikan Biologi, 2024)
News of the water crisis can be found all over the world, including Indonesia. Unfortunately, the knowledge of the younger generation about the importance of springs, including Ndhas Gendhing, is still low because the knowledge is passed on orally rather than in writing. Indigenous knowledge about Ndhas Gendhing is still maintained by the people of Sukorejo Village. The aim of this research is to study Ndhas Gendhing Spring using ethnoecological principles. The research method was field research. There are four types of plants that have the potential to protect the Ndhas Gendhing spring, namely Preh (Ficus macrocarpa), Ringin (Ficus benjamina), Pring Jawa (Gigantochloa atter), and Pring Petung (Dendrocalamus asper). There are nine aquatic animal species found in the water source, namely Lele lokal (Clarias batrachus), Wader (Rasbora argyrotaenia), Peto (Aplocheilus armatus), Nila (Oreochromis niloticus), Yuyu (Parathelphusa convexa), Melem (Rasbora caudimaculata), Kotes (Channa limbate), Deleg (Channa striata), dan Pelus (Anguilla sp.). Based on the physical and chemical characteristics, the water is odorless and clear. The average pH was 6.92, with an average TDS of 117.6 ppm. This means that the water condition is in the excellent category. The abundant water can be used for daily needs such as bathing, washing clothes, and PDAM drinking water. In fact, there are special rituals such as padusan and kungkum. It is hoped that the younger generation's awareness of the existence of the Ndhas Gendhing spring will support sustainable water security.